2019
DOI: 10.18038/aubtda.411727
|View full text |Cite
|
Sign up to set email alerts
|

Application of Recuperator for Waste Heat Recovery From Exhaust Flue Gas in Hot Water Boiler in the Central Heating Plant

Abstract: In general, the outgoing exhaust gasses are released to atmosphere at over temperature of the dew point of water vapor in waste gases. It is well known that recovering a portion of the waste heat enhances the efficiency of boilers and provides fuel savings. In this study, the potential of recovering waste heat emitted by the hot water boiler chimney in a central heating plant of a selected university was investigated. Energy losses were calculated for six months that the central heating system was in full-load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Several studies in different industries have demonstrated the potential benefits of WHR technologies in improving energy efficiency and reducing environmental impacts. For example, a study conducted in a biscuit factory in Turkey reported energy savings of 27.13 tons of CO 2 emissions per year using economizers to recover waste heat from their boiler [26]. Similarly, installing WHR technology in industrial boilers in Malaysia's paper and pulp industries achieved savings of 2150 tons of CO 2 per year [27], comparable to the observed reduction of 866.70 tons of CO 2 emissions per year in the KHS factory.…”
Section: Comparison Of the Findings With Other Studies In The Fmp Ind...mentioning
confidence: 89%
“…Several studies in different industries have demonstrated the potential benefits of WHR technologies in improving energy efficiency and reducing environmental impacts. For example, a study conducted in a biscuit factory in Turkey reported energy savings of 27.13 tons of CO 2 emissions per year using economizers to recover waste heat from their boiler [26]. Similarly, installing WHR technology in industrial boilers in Malaysia's paper and pulp industries achieved savings of 2150 tons of CO 2 per year [27], comparable to the observed reduction of 866.70 tons of CO 2 emissions per year in the KHS factory.…”
Section: Comparison Of the Findings With Other Studies In The Fmp Ind...mentioning
confidence: 89%
“…Thus, the energies of the flue gas without ( ) and with ( ) heat recovery are expressed, respectively, as given in Eqs. (5) , (6) [ 147 ]: where is the mass flow rate of the flue gas (kg/h), is the specific enthalpy at the flue gas temperature (kJ/kg), is the specific enthalpy of the flue gas at the ambient temperature (kJ/kg), and is the specific enthalpy of the flue gas after heat recovery (kJ/kg). Thus, the energy saved (kJ/h) by using WHR is expressed as: …”
Section: Economics Of Waste Heat Recoverymentioning
confidence: 99%
“…The expression for the accrued savings on fuel in kg/h is obtained from Karanfil et al [ 147 ]: where is the lower heating value of the fuel (kJ/kg), and is efficiency of the heating unit.…”
Section: Economics Of Waste Heat Recoverymentioning
confidence: 99%